EFEKTIFITAS KINERJA KOMITE MADRASAH DALAM PENINGKATAN MUTU PENDIDIKAN - Lisadiyah MF (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2009)
The education is well-administered in the event that Islamic school as education administration is able to provide a qualified teaching staff with the support of condition of the school environment and community surrounding the school which in fact lives in order and stability. This condition would be complete if; one of other determining factors, parents' involvement which in this matter is represented by the Islamic school committee is also able to perform properly its four main functions as advisory agency, supporting ageng, controlling agent', and mediator. This research attempts to measure the effectiveness of performance of Islamic committee by way of observing the extent to which the foregoing functions may be appropriately performed.